Analysis of Product Flow Mechanism, Information, and Finance in the Supply Chain of Fourfinger Threadfin Fish (Eleutheronema tetradactylum) in Tanah Merah Village, Tanah Merah District, Indragiri Hilir Regency - Asmara, Elsi Chyntia; Yulinda, Eni; Bathara, Lamun (Jurnal Perikanan dan Kelautan, 2024)
Tanah Merah Village is one of the Fourfinger threadfin fish-producing areas. Most of the population works as fishermen as the basis of their economic income. Fourfinger threadfin fish is the main fishery commodity and has high economic value, thus encouraging the sustainable use of Fourfinger threadfin resources. This research aims to analyze the product flow, information, and finance mechanism in the supply chain of fourfinger threadfin (Eleutheronema tetradactylum) from Tanah Merah Village, Tanah Merah District, Indragiri Hilir Regency. The method used was in-depth interviews with a qualitative approach. The research results show that the flow of fourfinger threadfin fish products is spread across four provinces on the island of Sumatra. The payment systems used are cash, bank transfers, and loans. The selling price of delighted fish at the fisherman level is IDR 45.000/kg, and at the end consumer IDR 55.000-70.000/kg. Five Senangin fish supply chain entities, namely fishermen, fishermen, collectors, retailers, and final consumers form 3 chain patterns. The longest chain involves five entities and the shortest three entities. The farmer's share value for fishermen is relatively high at over 60%, with the highest value in chain three at 81.8%, indicating the most efficient chain. The product, financial, and information flow mechanisms have been running well. However, coordination and information integration still need to be improved to optimize the supply chain for fourfinger threadfin fish Tanah Merah Village